Marketing Communication Strategy of the Rice Bowl Products in Pontianak City - Rizqi Rusmana Putri; Bob Andrian; Evi Hafizah; Nindya Juwita Utimadini (International Journal of Media and Communication Research (IJMCR), 2022)
The purpose of this study is to identify and explain the marketing communication strategy used by Mbok Dower MSMEs in Pontianak in increasing product sales of Rice Bowl. The main theory used in this study uses the Marketing Communication theory proposed by Kotler. This research methodology uses a qualitative approach, a descriptive method in order to explain the focus and objectives of the research regarding the marketing communication strategy used by Mbok Dower MSMEs Pontianak in increasing sales. The results showed that the marketing communication strategy in increasing sales of their Rice Bowl products in Pontianak are such as: Combining three marketing communication strategies in the form of: marketing communications, sales marketing, and marketing events in marketing their business products, segmenting, targeting, and positioning so that the products sold are able to compete with similar businesses and are able to reach targeted consumers in marketing products. Owner Mbok Dower also implements a marketing mix consisting of product, price, place and promotion in which it is assisted by the use of social media, Instagram, as an alternative promotional media that can reach the entire Pontianak community and has been proven to survive even though it was affected by the Covid-19 pandemic.